A Literature Study On The Elements Of English Learning Curriculum - Aulia Rahmi; Siminto Siminto; Zaitun Qamariah (BADAN PENERBIT STIEPARI PRESS, 2023)
This writing aims to determine the importance of learning English curriculum in schools. In this writing using the method of literature review (library research). English is a very important skill. Learning English well is no longer an optional skill, it can improve the students' overall quality. Teachers should guide students to re-understand English from the perspective of general education so that students are willing to learn English well. From the discussion it can be concluded that the English learning curriculum in schools is very important. This is based on the communication skills that students get, not only limited to knowledge, students will be motivated and feel that what they have learned can be useful and used in language. Learning English is developing the ability to speak English contextually and in accordance with the context and the daily conditions and situations of students. This is to produce a form of learning English that is more in touch with the language needs of students. These findings need to be integrated in such a way as to produce learning activities that emphasize aspects of how English is used as a communication tool that suits the needs of students.